Population turnover in groups of wing-moulting waterbirds: the use of a natural marker in Great Crested Grebes - Piersma, Theunis (Wildfowl, 1987)
Flapping the wings is a common comfort behaviour in waterbirds. It is easy to see whether a bird is in wing-moult or not, and to see the extent of feather renewal. Since each moult phase takes a definitive number of days, wing-moulting waterbirds are naturally marked in successive cohorts. Combining observations on moult phase with data on the numbers present, it is possible to calculate minimum rates of emigration and immigration of moulting individuals (turnover). In August-October 1985 and 1986 the method was applied on a population of Great Crested Grebes Podiceps cristatus moulting in Lake IJsselmeer, The Netherlands. Only the possible range in the extent of population turnover could be determined. In both study years, the best approximation of the total numbers of grebes that had been present while in wing-moult, was almost twice the average number recorded. With more information on the variability in wing-flapping bout rates, the method has great potential for studies of moulting waterbirds in sites or habitats where they are difficult to study otherwise.